THE INFLUENCE OF INDONESIAN PROSODIC FEATURES ON ENGLISH WORD STRESS PRODUCTION - Rudha Widagsa; Sri Wiyanah; Primasari Wahyuni (English Review: Journal of English Education, 2019)
Generally, word stress tends to be ignored and is not considered a serious problem in Indonesian EFL; most teachers only focus on lexical and grammatical aspects of English. In fact, the prosodic features existing in English greatly affect meaning. This research, therefore, is intended to find out how Indonesian Learners of English (ILE) produce the English word stress. The stressed syllables were identified by using the highest pitch in each word. This research involved 20 respondents whose mother tongue is Indonesian. PRAAT software was applied to analyze the recordings, including measuring the pitch of each word. Word stress is indicated by the highest pitch of each word. The lowest pitch indicates weak stress. The result illustrated that ILE produces inappropriate word stress in second language learning. Most of them are not able to distinguish between strong and weak stressed syllables. This is because in their native language, prosodic features, such as word stress, do not prevail. Thus, English word stress production was heavily influenced by Indonesian features of stress. From the 36 words that become the instrument of this research, less than 50% were pronounced correctly, in most cases, and the highest pitch fell on last syllables. The absence of prosodic features in Indonesian language and limited knowledge on English phonetics drive the ILE to pronunciation error.